Design and Evaluation of Buffered Triple Modular Redundancy in Interleaved-Multi-Threading Processors - Marcello Barbirotta; Abdallah Cheikh; Antonio Mastrandrea; Francesco Menichelli; Mauro Olivieri (IEEE Access, 2022)
Fault management in digital chips is a crucial aspect of functional safety. Significant work has been done on gate and microarchitecture level triple modular redundancy, and on functional redundancy in multi-core and simultaneous-multi-threading processors, whereas little has been done to quantify the fault tolerance potential of interleaved-multi-threading. In this study, we apply the temporal-spatial triple modular redundancy concept to interleaved-multi-threading processors through a design solution that we call Buffered triple modular redundancy, using the soft-core Klessydra-T03 as the basis for our experiments. We then illustrate the quantitative findings of a large fault-injection simulation campaign on the fault-tolerant core and discuss the vulnerability comparison with previous representative fault-tolerant designs. The results show that the obtained resilience is comparable to a full triple modular redundancy at the cost of execution cycle count overhead instead of hardware overhead, yet with higher achievable clock frequency.